2019
DOI: 10.3390/nu11081918
|View full text |Cite
|
Sign up to set email alerts
|

Native Hypovitaminosis D in CKD Patients: From Experimental Evidence to Clinical Practice

Abstract: Native hypovitaminosis D (n-hVITD) is frequently found from the early stages of chronic kidney disease (CKD) and its prevalence increases with CKD progression. Even if the implications of n-hVITD in chronic kidney disease-mineral bone disorder (CKD-MBD) have been extensively characterized in the literature, there is a lot of debate nowadays about the so called “unconventional effects” of native vitamin D (25(OH)VitD) supplementation in CKD patients. In this review, highlights of the dimension of the problem of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…In the clinical setting, chronic kidney disease is an illness of particular interest with respect to vitamin D and CVD: primarily, because both low circulating 25(OH)D and low 1,25(OH) 2 D concentrations are frequent findings in CKD patients [ 93 , 94 ]; secondly, because the risk of vascular calcification and CVD is substantially higher in patients with CKD than in individuals with preserved kidney function [ 95 ]; and thirdly, because impaired kidney function is considered to contribute to the loss of homeostatic control of serum calcium concentrations and may thus influence the cut-off point defining the toxicity of vitamin D and calcium [ 15 ]. There is evidence that vitamin D administration of >2000 IU/d vitamin D or activated vitamin D significantly increased concentrations of the cardiovascular risk marker FGF-23, especially in patients with end-stage kidney/heart failure [ 96 ].…”
Section: Cardiovascular Events In Patients With Chronic Kidney Dismentioning
confidence: 99%
“…In the clinical setting, chronic kidney disease is an illness of particular interest with respect to vitamin D and CVD: primarily, because both low circulating 25(OH)D and low 1,25(OH) 2 D concentrations are frequent findings in CKD patients [ 93 , 94 ]; secondly, because the risk of vascular calcification and CVD is substantially higher in patients with CKD than in individuals with preserved kidney function [ 95 ]; and thirdly, because impaired kidney function is considered to contribute to the loss of homeostatic control of serum calcium concentrations and may thus influence the cut-off point defining the toxicity of vitamin D and calcium [ 15 ]. There is evidence that vitamin D administration of >2000 IU/d vitamin D or activated vitamin D significantly increased concentrations of the cardiovascular risk marker FGF-23, especially in patients with end-stage kidney/heart failure [ 96 ].…”
Section: Cardiovascular Events In Patients With Chronic Kidney Dismentioning
confidence: 99%
“…Also, "the fibroblast growth factor 23 (FGF23), as well as its co-receptor α-Klotho, may favourably affect CYP24A1 activity in response to hypercalcemia and hyperphosphatemia. Because of its critical involvement in regulating the levels of 1,25(OH)2D3 in the circulation, the extent of research into CYP24A1's significance in this regard has been widespread [21][22] . Mice lacking the CYP24A1 gene showed a much greater degree of impairment in 1,25(OH)2D3 and 25(OH-D3) pharmacokinetics than did mice that were heterozygous for the CYP24A1 gene.…”
Section: Role Of Cyp24a1 In Vitamin D Catabolismmentioning
confidence: 99%
“…On the other hand, glutathione peroxidase deficiency in kidney diseases contributed to the development of cardiac diseases risk due to an increase in ROS generation and inflammatory pathways [ 152 ]. Furthermore, CKD patients also display hypovitaminosis D [ 153 ] as well as hypoalbuminemia [ 154 ] and zinc deficiency [ 155 ].…”
Section: H 2 S As a Signaling Mediator In The Kmentioning
confidence: 99%
“…On the other hand, glutathione peroxidase deficiency in kidney diseases contributed to the development of cardiac diseases risk due to an increase in ROS generation and inflammatory pathways [152]. Furthermore, CKD patients also display hypovitaminosis D [153] as well as hypoalbuminemia [154] and zinc deficiency [155]. Fascinatingly evidence demonstrated that NaHS suppresses the expression of the ROS-generating enzyme, NADPH oxidase (NOX) and its essential subunit, Rac-1, in cultured vascular smooth muscle cells [156].…”
Section: Antioxidant Role Of H 2 Smentioning
confidence: 99%